Regulation of Bacteroides acidifaciens by the aryl hydrocarbon receptor in IL-22-producing immune cells has sex-dependent consequential impact on colitis - Mitchell, Chandani; Staley, Shanieka; Williams, Michal Claire; Saxena, Archana; Bogdon, Raymond; Roark, Kasie; Hailey, Michele; Miranda, Kathryn; Becker, William; Dopkins, Nicholas; Pena, Maria Marjorette; Hogan, Kristen M.; et al. (Frontiers in Immunology, 2024)
Colitis is an inflammatory bowel disease (IBD) characterized by immune cell dysregulation and alterations in the gut microbiome. In our previous report, we showed a natural product in cruciferous vegetables and ligand of the aryl hydrocarbon receptor (AhR), indole-3-carbinol (I3C), was able to reduce colitis-induced disease severity and microbial dysbiosis in an interleukin-22 (IL-22) dependent manner. In the current study, we performed single-cell RNA sequencing (scRNAseq) from colonocytes during colitis induction and supplementation with I3C and show how this treatment alters expression of genes involved in IL-22 signaling. To further define the role of IL-22 signaling in I3C-mediated protection during colitis and disease-associated microbial dysbiosis, we generated mice with AhR deficiency in RAR-related orphan receptor c (Rorc)-expressing cells (AhR ΔRorc ) which depletes this receptor in immune cells involved in production of IL-22. Colitis was induced in wildtype (WT), AhR ΔRorc , and littermate (LM) mice with or without I3C treatment. Results showed AhR ΔRorc mice lost the efficacy effects of I3C treatment which correlated with a loss of ability to increase IL-22 by innate lymphoid type 3 (ILC3s), not T helper 22 (Th22) cells. 16S rRNA microbiome profiling studies showed AhR ΔRorc mice were unable to regulate disease-associated increases in Bacteroides, which differed between males and females. Lastly, inoculation with a specific disease-associated Bacteroides species, Bacteroides acidifaciens (B. acidifaciens), was shown to exacerbate colitis in females, but not males. Collectively, this report highlights the cell and sex-specific role of AhR in regulating microbes that can impact colitis disease.